Food Insecurity and Academic Disruption Among College Students. Issue 4 (2nd October 2018) - Phillips, Erica; McDaniel, Anne; Croft, Alicia
Abstract : Food insecurity is a growing problem among college students, but little is known about how it is related to academic outcomes. We analyze broad demographics of food insecurity at one institution and explore how food insecurity is associated with whether students have neglected their academics, reduced courses, or considered dropping out of college due to their finances. We then discuss programs that may support food insecure students.